Investigating students' reasoning over time for case comparisons of acyl transfer reaction mechanisms. Issue 2 (14th January 2021) - Watts, Field M.; Zaimi, Ina; Kranz, David; Graulich, Nicole; Shultz, Ginger V.
Abstract : Reasoning about organic chemistry reaction mechanisms requires engagement with multiple concepts and necessitates balancing the relative influence of different chemical properties. A goal of organic chemistry instruction is to support students with engaging in this type of reasoning. In this study, we describe our use of case comparison problems to elicit students' reasoning about acyl transfer reaction mechanisms across a semester. Using an instrumental case study methodology, we analysed three students' reasoning across three time points: in a pre-interview at the beginning of the semester, on their written responses to one implementation of an in-class scaffold activity, and in a post-interview near the middle of the semester. Through the theoretical lens of Hammer's resources framework, we analysed the resources that students activated when approaching the case comparison problems. We characterized how students used each resource to support their reasoning, alongside characterizing how students weighed the different resources they activated. Our findings indicate that the case comparison problems activated a number of resources for each student across the time points by encouraging students to relate the surface-feature differences between reactions with the associated underlying properties. Students generally used resources, such as resonance and steric effects, in similar ways to support their reasoning across the time points. The study also illustrates the range in students' abilities to weigh multiple conceptual influences and how this ability might change across the semester. This case study has implications for future research exploring how students reason with multiple concepts and for instructors seeking to implement activities that support students' reasoning with case comparison problems.